Prognostic Value of Urinary Calprotectin, NGAL and KIM-1 in Chronic Kidney Disease - Felix S. Seibert; Maximilian Sitz; Jürgen Passfall; Martin Haesner; Peter Laschinski; Martin Buhl; Frederic Bauer; Nina Babel; Nikolaos Pagonas; Timm H. Westhoff (Karger Publishers, 2018)
Background/Aims: Urinary biomarkers like neutrophil gelatinase-associated lipocalin (NGAL) and kidney injury molecule-1 (KIM-1) do not only allow an early diagnosis of acute kidney injury, but also provide prognostic information in this setting. The present prospective study investigates, whether the urinary biomarkers NGAL, KIM-1 and calprotectin have prognostic information in chronic kidney disease (CKD) as well. Methods: Urinary calprotectin, NGAL and KIM-1 concentrations were assessed in a study population of 143 patients with stable CKD comprising diabetic and hypertensive nephropathy, glomerulonephritis/vasculitis, and autosomal dominant polycystic kidney disease. An eGFR fluctuation > 5ml/min/1.73m2 in the past 12 months was defined as an exclusion criterion in order to exclude cases with acute on chronic kidney injury. Renal function was monitored for a median follow-up of 37 months. Results: In the overall study population, all the three biomarkers failed to predict DeGFR and DACR from baseline to follow-up in linear regression analysis adjusted for age, gender, and baseline eGFR. Contrarily, baseline ACR was significantly associated with DeGFR (p< 0.001). In the subgroup of patients with vasculitis and glomerulonephritis, all the three biomarkers were significantly associated with DeGFR, with calprotectin having the highest regression coefficient. Conclusion: In contrast to the traditional biomarker "albuminuria", neither the inflammatory biomarker calprotectin, nor the tubular biomarkers NGAL and KIM-1, provide robust prognostic information on the loss or renal function in a heterogeneous CKD population. All of them, however, are candidate prognostic biomarkers in primarily inflammatory renal diseases.